Feasibility Analysis for Investment of Cargo Village Development in Soekarno-Hatta International Airport - Meutia Damai Nurlita; Dian Masyita; Yudi Ahmad Faisal (Jurnal Manajemen dan Bisnis, 2021)
The sector of world air cargo industry has become broader becoming one of the most integral parts of the global economy, as a significant airport company in Indonesia, PT Angkasa Pura II (Persero), AP2, builds Cargo Village of the Soekarno-Hatta International Airport to provide the best air cargo service providers to meet the competition in the global market. This research aims to investigate the most suitable Construction Staging scenario of the Cargo Village construction project for investment decision by using business issue analysis and financial analysis. This study uses mixed methodology, a combination of qualitative and quantitative research methods. The qualitative method in this study aims to assess the external conditions and AP2 resources, by TOWS Analysis method. Meanwhile, quantitative research methods are used to conducting Financial Feasibility in form of Capital Budgeting Payback Period (PP), Net Present Value (NPV) and Internal Rate of Return (IRR) for several scenarios of development staging. The result shows that AP2 continuously improves its capabilities and core competencies as the internal strength to balance the threat from outside the company and is prepared to start taking advantage of the opportunity available from the external environment to gain more knowledge to take a new step for comprehensive cargo business. the construction of Cargo Village is feasible to be done by the three scenarios of development staging. This research found that Development scenario of finishing the construction on the main cargo terminal building, which has the biggest investment cost prior to the construction of warehouse and additional services such as perishable and transhipment, gives the best result with the largest value of NPV & IRR and less payback period.